Daylit offices: A comparison between measured parameters assessing light quality and users' opinions. (15th February 2017) - Bellia, Laura; Fragliasso, Francesca; Stefanizzi, Emanuela
Abstract: The paper reports data referred to luminance and illuminance measurements performed in three offices located in Naples (latitude 40°51′ N, longitude 14°14′ E). Luminance maps are obtained through HDR imaging technique by means of a video-luminancemeter. Then users' opinions about comfort conditions in their workplaces are analyzed in typical days and compared with illuminances measured at the eye level and at the workplane and with some daylight performance indexes (Useful Daylight Illuminance and Daylight Glare Probability). Results demonstrate that, given a particular space, similar luminance trends can be observed when specific weather conditions occur. Moreover discomfort turns out to be referred to precise moments of the day and to particular weather conditions. A correspondence between daylight performance indexes and users' opinions is not always observed. Highlights: Similar luminance trends can be observed when specific weather conditions occur. Given a space, visual discomfort occurs in specific moments of the day. Direct sunlight turns out to be the factor that mainly affects visual discomfort. A correspondence between comfort indexes and users' opinions is not always observed.